A Systematic Review on Bibliotherapy and Its Effectiveness in Psychotherapeutic Dimension - Lin, Ximeng (Transactions on Social Science, Education and Humanities Research, 2024)
This review began with the current educational background and mainly focused on emotional education. Noting the pressure exerted on human beings from the development of various industries as well as the needs of society, it associated the popular topics of education and stress coping with mental health, and examined bibliotherapy as a correlative item between them. Bibliotherapy is a type of creative art therapy that uses reading materials as a medium for psychotherapy and has similar concepts to other psychotherapies, including transference, countertransference, potential space, and the capability to play. This paper explained and analyzed bibliotherapy following the logic from the definition, purpose, advantage, and therapeutic principle, to its effectiveness, and hoped to provide an introduction to bibliotherapy for the general public by doing a systematic literature review. The research suggested that bibliotherapy as a low-cost, effective and timely (saving waiting time) method can be broadly promoted, but the specific choice of books needed to be considered individually for each person’s own circumstances.